Effects of paddle dimensions on shoulder joint torque for a swimmer with unilateral transradial deficiency - Nakashima, M.; Chida, Y. (Sports Engineering, 2023)
To improve a training paddle during the crawl stroke for swimmers with unilateral transradial amputation/deficiency, the paddle dimensions should be determined considering the balance of increases in shoulder joint torques between the intact and amputated/deficient limbs. The objectives of this study were (i) to propose a new index which was the ratios of increased effort at shoulder joints when attaching paddles for the intact and deficient limbs, (ii) to investigate the effects of the paddle dimensions on the index by simulation, and (iii) to design and fabricate an actual paddle based on the determined dimensions. The actual paddle was tested by a participant to confirm its validity. From the parameter study, it was found that the index increased according to the increase in paddle size as well as the length of the forearm section of the paddle. It was also found that the index became close to 1 when the angle of the forearm section was 30 degrees under conditions where the paddle size and the length of the forearm section were appropriate values. From the comparative study, it was found that the present paddle with the appropriate dimensions was best for the index of the shoulder joint torque, and satisfactory for swimming speed and propulsive efficiency. The experiment with the participant using the actual paddle supported those positive results since a higher score of evaluation and swimming speed were obtained for the present paddle.